Study of the positional cross-section of acoustic wave scattering for a system of sound-permeable spheres - Насибуллаева, Эльвира (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2024)
In the frame of solving the acoustic scattering problem on a system consisting of many sound-permeable spheres, one of the main characteristics of the scattering phenomenon, namely, the positional scattering cross-section, is investigated. This characteristic allows one to analyze the intensity of a scattered wave in a fixed direction. The formula for this characteristic is transformed in the case of many scatterers, taking into account the interaction between the spheres in the system. This formula is applicable to any number of spheres in the system and their arbitrary distribution in 3D space. Two types of external pressure are considered — a plane wave and a spherical wave from a monopole radiation source. The numerical algorithm is verified with the data of other numerical studies; qualitative agreement between the results is obtained. Numerical parametric analysis for a system consisting of two sound-permeable spheres showed that in the case when the density of the medium inside the spheres is much less than the surrounding medium, the system has the best scattering properties; backscattering in a system with spheres of the same radius is higher than in a system with spherical particles of different sizes; for a plane wave, an increase in the wave radius leads to a decrease in the value of the backscattering cross-section function, while for a monopole radiation source, an increase in the wave radius leads to an increase in this value. For a system containing a 121 drop of water in air, it was found that an increase in the distance between the centers of the spheres leads to an increase in the scattering properties of this layer in the opposite direction.